The Effectiveness Of The Brain Based Teaching Approach In Dealing With Problems Of Form Four Students' Conceptual Understanding Of Newtonian Physics - Saleh, Salmiza (Penerbit Universiti Sains Malaysia, 2011)
The aim of this study was to assess the effectiveness of the Brain Based Teaching Approach in dealing with problems related to form four students' conceptual understanding of Newtonian Physics, as currently taught in secondary schools. Techniques implemented in this study were based on the Brain Based Learning Principles developed by Caine and Caine (1991, 2003), Jensen (1996) and Sousa (1995). Using a brain compatibility strategy, the study paid specifc attention and consideration on seven main areas: (i) activation; (ii) clarifcation of the outcome and painting the big picture of the lesson; (iii) making the connection; (iv) doing the learning activity; (v) demonstration of student understanding; (vi) review of student recall and retention/ closure; and (vii) previewing the new topic. The effectiveness of this Brain Based Teaching Approach within the targeted context was then assessed in a quasi-experimental research method involving 100 students from two Science Secondary Schools in northern peninsular Malaysia. Data collected from the results, based on the Test of Newtonian Physics Conceptual Understanding, were analysed descriptively and inferentially, using an independent sample t-test technique. The fndings of the research showed that this teaching approach was effective in dealing with the problems mentioned. It was found that students who followed the Brain Based Teaching Approach possessed a better conceptual understanding of Newtonian Physics compared to students who were exposed to conventional teaching methods